Different requirements for membrane fusion mediated by the envelopes of human immunodeficiency virus types 1 and 2. - Dragic, T (1993)
CD4+ cells derived from the human cell lines U87MG and SCL1 cannot be infected by human immunodeficiency virus type 1 (HIV-1) or fuse with cells expressing the HIV-1 envelope. This block was complemented in heterokaryons with HeLa cells and probably reflects the absence of cellular factors necessary for membrane fusion. Since U87MG cells expressing CD4 are permissive to HIV-2, distinct cellular factors could be required for fusion mediated by two related human retroviruses.